Implementation Of Digital Content About Sacred Bali As A Means Of Education For Tourists In Preserving The Culture Of The Island Of Bali - Selamet, I Wayan Agus; Satia Negara, I Made Weda; Paristha, Ni Putu Tiya; Rusadi, Ni Wayan Purnami; Hendrayani, Ni Kadek Sri (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
The in this study aims to discuss the application of digital content about sacred bali as a means of education for tourists in preserving the culture of bali island. The formulation of the problem in this study is how is the effectiveness of digital content about sacred Bali as a means of education for tourists in preserving Balinese culture and how is the role of tourism industry players in implementing digital content about sacred bali as a means of education for tourists in preserving Balinese culture. the methodology in this study uses data collection through observation, interviews, and literature studies. the sampling technique in determining informants in the interview uses purposive sampling. The data analysis used in this study is a qualitative descriptive analysis which has five stages, the first is data collection, the second is summarizing data, the third is adjusting data, the fourth is explaining data, the fifth is drawing conclusions based on theory. The results of the study show that there are four indicators that make digital content about sacred Bali effective to implement, including Reader Cognition, Sharing Motivation, Persuasion, Life Factors. And there are two actors in the tourism industry who have an important role in implementing digital content of sacred Balinese culture, including travel agents and the second is the local community as the god of the house.